2022
DOI: 10.1177/08862605221078816
|View full text |Cite
|
Sign up to set email alerts
|

BYSTANDER INTERVENTION AMONG DRINKING GAMERS Bystander Intervention Among College Student Drinking Gamers: Sexual Assault Attitudes, Self-Efficacy, and Intent to Intervene

Abstract: Heavy drinking and sexual assault warrant significant concern on U.S. college campuses as emerging evidence suggests that the risk for sexual victimization is amplified in the context of high-risk drinking behavior. Despite recent attention to sexual assault (e.g., MeToo Movement), rates of perpetration remain largely unchanged. In applying the bystander intervention framework, our understanding of the relation between key factors that may facilitate or prevent behavioral action, or when and how these factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 71 publications
1
4
0
Order By: Relevance
“…In this study, the social self-efficacy showed a significant difference between the experienced group and the non-experienced group of witnessing sexual violence situations; the higher the social self-efficacy, the higher the experience of witnessing the sexual violence situation (by about 2.2 times). This result supports previous studies which found that, as self-efficacy increased, the bystander's intention to intervene increased [32].…”
Section: Discussionsupporting
confidence: 91%
“…In this study, the social self-efficacy showed a significant difference between the experienced group and the non-experienced group of witnessing sexual violence situations; the higher the social self-efficacy, the higher the experience of witnessing the sexual violence situation (by about 2.2 times). This result supports previous studies which found that, as self-efficacy increased, the bystander's intention to intervene increased [32].…”
Section: Discussionsupporting
confidence: 91%
“…Findings are more plentiful, if conflicting, regarding how bystander’s general alcohol use affects their responses to SA situations. Six studies found no relationship between bystander’s alcohol use (typical drinking frequency, alcohol use disorders score, binge drinking, problem drinking, drinking games, and alcohol expectancies) and bystander behavior, intentions, or peer norms (Austin et al, 2016; Fleming & Wiersma-Mosley, 2015; Intagliata, 2017; Pazienza, 2021; Powers et al, 2015; Williams et al, 2021). Four studies found that bystanders who drink more (typical drinking frequency and binge drinking) exhibited fewer bystander behaviors, lower intentions, and more negative perceived consequences of bystander behavior (Fleming & Wiersma-Mosley, 2015; Orchowski et al, 2016; Palmer, 2016; Schipani-McLaughlin et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Studies frequently labeled proximal proxies of bystander behavior with names that can be misleading out of context, including bystander intervention behavior (Burn, 2009); bystander intervention (Fleming & Wiersma-Mosley, 2015; Hoffman & Daigle, 2020); bystander attitudes (Intagliata, 2017; McMahon, 2010; Pazienza, 2021; Powers et al, 2015); bystander inaction (Katz, 2015); direct bystander intervention (Katz & Nguyen, 2016); bystander non-intervention (Katz et al, 2018); in-the-moment response (Steel et al, 2022); and behavioral interventions (Zelin et al, 2019). In Supplemental Appendix A, we include the measure name as it appears in the study but with a descriptor in brackets (willingness, intentions, or difficulty) to reduce confusion.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations